Assessment of a new benzylidene-based corrosion inhibitor for X60 carbon steel in 1 M HCl medium: Experimental and computational studies - Nkem B. Iroha; Cordelia U. Dueke-Eze; Valentine Chikaodili Anadebe; Ngozi J. Maduelosi; Renjith Thomas; Eno E. Ebenso (Results in Surfaces and Interfaces)
The performance of the studied compound in this work namely, N-(5-nitro-2-hydroxybenzylidene) pyridine-2-amine (NH2PA) as an inhibitor for X60 steel corrosion in 1 M HCl was appraised via weight loss and electrochemical methods. The results revealed that NH2PA possessed excellent corrosion inhibition capability which increased with rise in its concentration. An inhibition efficiency of 97.3 % was attained at a low concentration (1.0 mM NH2PA). In addition, the elevation of solution temperature indicated a decline in the inhibition efficiency. Results from electrochemical test showed that the inhibitive behavior NH2PA was mixed type. The adsorption of NH2PA inhibitor system onto the X60 steel surface followed the Langmuir adsorption isotherm, showing a combined physical and chemical adsorption on the X60 steel surface. The surface morphology and adsorption of the inhibitor on the steel surface were confirmed using SEM. Theoretical computations were studied utilizing density functional theory (DFT) to aid in better evaluation of the inhibition mechanism and performance of NH2PA.